High-Fat Diet Impact on T Cell Polarization in First Degree relative (FDR) Subject with Type 2 Diabetes Mellitus - Dini Aulia Cahya; Heri Wibowo; Alida Rosita Harahap (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: The prevalence of high-fat diet consumption that triggered obesity is increasing in last 2 decades. Type 2 diabetes mellitus is associated by the increasing number of inflammation marker, Acute phase protein in blood serum. In type 2 diabetes mellitus, combination of lifestyle and genetic factors is the most influential factors. Due to that fact, person with First Degree Relative ( FDR) in type 2 diabetes mellitus has the higher risk to develop into type 2 diabetes mellitus. T cell is one of leucocyte that has a significance role in adaptive immune response.T cell polarization will show the profile of adaptive immune response in chronic inflammation Objective: This study is purposed to analyse how T cell polarized in First Degree Relative (FDR) subject in risk of type 2 diabetes mellitus with high fat diet treatment.Methods: 30 Non-FDR subjects and 30 FDR subjects who included in parameter inclusion were treated with 250 mL whipping cream per day in 5 days. Pre and post treatment blood collection were tested for blood profile and flowcytometry intraseluler staining.Results: BMI is significantly increasing in Non-FDR subject meanwhile Cholesterol and HDL are significantly increasing in FDR subject. There are no significant changes in T cell subset including Th1, Th2, Th17 and Treg.Conclusion: Short term high fat diet treatment in 5 days increased some metabolic profiles on both group but there are no significantly different changes in T cell polarization.